2014
DOI: 10.4067/s0717-95532014000200006
|View full text |Cite
|
Sign up to set email alerts
|

Eventos Adversos Identificados Nos Relatórios De Enfermagem Em Uma Clínica Pediátrica

Abstract: Objetivo: Identificar os eventos adversos ocorridos na unidade de pediatria de um hospital de ensino de Goiânia-Goiás-Brasil. Método: Pesquisa descritiva, retrospectiva e documental, com abordagem quantitativa. A coleta foi realizada em dois períodos: outubro de 2011 a fevereiro de 2012 e em agosto de 2014. Os dados foram obtidos de relatórios de enfermagem preenchidos no período de junho de 2006 a junho de 2013. A análise estatística foi realizada no programa SPSS, versão 19.0 for Windows. Resultados: Foram i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 9 publications
(7 reference statements)
1
2
0
2
Order By: Relevance
“…The hospital professionals in the scenario of this research, through spontaneous notifications, indicated the main causes for the occurrence of incidents were factors related to noncompliance with the routine/protocol and also outlined actions that they consider pertinent to avoid recurrence of incidents, such as: modifications to the routine/protocol, and provide orientation and training. The national and international literature on the subject corroborates these findings (1)(2)(3)6,8,22) . Human resources and quality management managers should be in continuous contact with the hospital staff in order to obtain feedback on patient safety in terms of training and management of teams.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…The hospital professionals in the scenario of this research, through spontaneous notifications, indicated the main causes for the occurrence of incidents were factors related to noncompliance with the routine/protocol and also outlined actions that they consider pertinent to avoid recurrence of incidents, such as: modifications to the routine/protocol, and provide orientation and training. The national and international literature on the subject corroborates these findings (1)(2)(3)6,8,22) . Human resources and quality management managers should be in continuous contact with the hospital staff in order to obtain feedback on patient safety in terms of training and management of teams.…”
Section: Discussionsupporting
confidence: 70%
“…It is also important for the institution to provide technologies that favor this improvement. These recommendations are indicated in national (2,8) and international studies (1,3) , collaborating to prevent incidents and their recurrence (3) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Si bien es cierto, que todos los pacientes están en condiciones de vulnerabilidad ante el error humano de quienes los cuidan, los niños lo son aún más (11,30). Asimismo, la literatura reporta que en los niños, existe mayor riesgo de infecciones, flebitis, úlceras por presión y errores con la administración de medicamentos, por lo cual resulta favorecedor abordar no solo su caracterización , sino además, analizar factores de riesgo y estrategias para minimizarlos, con el propósito de acercar tales alternativas a nuestro contexto, proporcionando a los profesionales estrategias basadas en la evidencia de que se pueden implementar en el quehacer del cuidado de enfermería.…”
Section: Introductionunclassified
“…No cenário de atuação da enfermagem pediátrica, o cuidado sistematizado e individualizado, que contemple a criança como ser biopsicossocial, dotada de valores a serem respeitados e necessidades a serem supridas, tem sido alvo de estudos. Esses buscam, nos moldes científicos, a valorização e validação de padrões estabelecidos na concepção da atmosfera de cuidado, alicerçada no conhecimento e na responsabilidade com a segurança do paciente, exigindo esforços conjuntos de gestores e profissionais de saúde, visando a garantia e qualidade da assistência (1) . Parte-se do pressuposto de que a Sistematização da Assistência de Enfermagem (SAE) enquadra-se como um atributo legal para organizar o trabalho profissional quanto ao método, pessoal e instrumentos, viabilizando, assim, a operacionalização do Processo de Enfermagem (PE).…”
Section: Introductionunclassified